The efficacy of a multimodal recovery strategy implemented after a high-intensity rugby league training session - Aben, H. G. J.; Hills, S. P.; Higgins, D.; Cooke, C. B.; Davis, D.; Jones, B.; Russell, M. (The Journal of Strength and Conditioning Research, 2023)
The efficacy of a multimodal recovery strategy implemented within 4 hours of rugby league (RL) training was investigated using repeated-measures, randomized, crossover methods in 10 professional academy RL players (age: 17 ± 1 years). Following standardized training (5,383 m covered, 350-m high-speed running, 28 repeated high-intensity efforts, 24 collisions), players completed a multimodal recovery (REC) strategy (i.e., ~640 kcal meal + ~1,285 kcal snacks or drinks, cold-water immersion, sleep hygiene recommendations) or control (i.e., ~640 kcal meal: CONT) practices. Isometric mid-thigh pulls (IMTP), countermovement jumps (CMJ), and wellness questionnaires were completed before (-3 hours) and after (+24, +48 hours) training. The recovery strategy influenced IMTP peak force (p = 0.026), but between-trial differences were undetectable. No other between-trial effects (all p > 0.05) were seen for IMTP, CMJ, or wellness variables. Training-induced reductions in CMJ peak power (-4 ± 6% vs baseline: 4,878 ± 642 W) at +24 hours (p = 0.016) dissipated by +48 hours. Fatigue and lower-body soreness reduced by 16 ± 19% (p = 0.01) and 32 ± 44% (p = 0.024) at +48 hours versus +24 hours, respectively. Relative to CONT (i.e., posttraining nutrition), the effects of a single bout of recovery practices appeared limited when implemented after RL-specific training. Therefore, when training included limited collisions, balanced postexercise meals appeared equally effective relative to a multimodal recovery strategy. Transient changes in performance and wellness variables after training may have implications for practitioners. Consecutive training sessions, including a high frequency and intensity of eccentric muscle actions, should be carefully planned, especially near match-play.